Outlook for CRISPR-based tuberculosis assays now in their infancy - Huang, Zhen; Zhang, Guoliang; Lyon, Christopher J.; Hu, Tony Y.; Lu, Shuihua (Frontiers in Immunology, 2023)
Tuberculosis (TB) remains a major underdiagnosed public health threat worldwide, being responsible for more than 10 million cases and one million deaths annually. TB diagnosis has become more rapid with the development and adoption of molecular tests, but remains challenging with traditional TB diagnosis, but there has not been a critical review of this area. Here, we systematically review these approaches to assess their diagnostic potential and issues with the development and clinical evaluation of proposed CRISPR-based TB assays. Based on these observations, we propose constructive suggestions to improve sample pretreatment, method development, clinical validation, and accessibility of these assays to streamline future assay development and validation studies.